City size distribution and growth - Andreas Kopp (Hamburg Institute of International Economics (HWWA), 2000)
We discuss theoretical approaches to study the relationship between the size distribution of a nation's cities and macroeconomic growth. The discussion is based on the hypothesis of the New Growth Theory that inter-personal spillovers of education and skills determine the long-run growth of the economy. Growth theory treats such externalities as being uniformly effective over national territories and completely internal to nation-state. This suggests a link to urban economics which has a long tradition of considering human capital externalities as driving forces of the growth of urban centers, with productivity increases inducing immigration. From the perspective of the urbanization literature long-run macroeconomic growth is thus determined by the functioning of cities as a catalysts for human capital accumulation. Theoretical avenues to the relationship between the development of cities of different sizes and aggregate growth can be distinguished according to whether the spillovers occur between different production sectors or just within a single sector. Empirical studies of the interrelationship have proven to be inconclusive. In view of the results of the empirical research, the character of inter-personal human capital spillovers depends much on the technological maturity of city industries and calls for taking account of industry-specific innovation cycles. More attention has also to be devoted to the question of the generality or sector-specificity of human capital in peculiar industries. – – Das Diskussionspapier präsentiert Ansätze zur theoretischen Analyse der Beziehung zwischen der Größenverteilung der Städte eines Landes und dem volkswirtschaftlichen Wachstum. Die Bedeutung einer solchen Beziehung ist abgeleitet aus der Hypothese der Neuen Wachstumstheorie, daß Externalitäten der Humankapitalbildung der Wirtschaftssubjekte das langfristige Wachstum einer Volkswirtschaft bestimmen. Im Unterschied zur Wachstumstheorie standen diese Externalitäten in der Stadtökonomik seit langem im Mittelpunkt der Forschung, auf der Grundlage ihrer ausschließlich lokalen Wirksamkeit. Die theoretischen Ansätze zur Explizierung des Zusammenhangs zwischen der Stadtstruktur eines Landes und seinem langfristigen Wachstum unterscheiden sich in der Frage, ob die Externalitäten sektorunabhängig oder sektorspezifisch sind. Empirische Studien zu dieser Frage führen zu keiner Ablehnung einer der beiden Ansätze. Die Ergebnisse dieser Studien legen nahe, daß die theoretische Forschung Innovationszyklen einzelner Sektoren berücksichtigen muß. Darüber hinaus ist von Bedeutung, in welchem Verhältnis die in einem Sektor nachgefragten Qualifikationen sektor-spezifisch oder sektor-ungebunden sind.
Keywords: 330; Stadtgröße; Stadtgeographie; Wirtschaftswachstum; Neue Wachstumstheorie; Agglomerationseffekt; Spillover-Effekt; Wirtschaftsstruktur; Theorie